Political Economy of Panchayats in South India - TIMOTHY BESLEY, ROHINI PANDE, VIJAYENDRA RAO (Economic and Political Weekly February 24, 2007, 2007)
Based on a study of some 500 villages in the four southern Indian states of Andhra Pradesh, Karnataka, Kerala and Tamil Nadu, this paper examines how the functioning of the panchayat system mandated by the 73rd amendment to the Constitution has had an impact on the economic status of villages and the households within them. The study finds that gram panchayats, created by this massive experiment in democratic decentralisation, have had an effect on the delivery of public services, for example, in the targeting of beneficiaries of welfare programmes, but also that positive outcomes are linked to the political elites thrown up by the system.